Glycopolymer Code Based on Well-Defined Glycopolymers or Glyconanomaterials and Their Biomolecular Recognition - Yilmaz, Gokhan; Becer, C. Remzi (Frontiers in Bioengineering and Biotechnology, 2014)
Advances in the glycopolymer technology have allowed the preparation of more complex and well-defined glyco-polymers/particles with several architectures from linear to globular structures (such as micelles, dendrimers and nanogels). In the last decade, functionalized self-assembled/decided nano-objects and scaffolds containing glycopolymers were designed to develop many biological and biomedical applications in diseases treatments such as pathogen detection, inhibitors of toxins and lectin-based biosensors. These studies will facilitate the understanding and investigation of the sugar code on the carbohydrate–lectin interactions, which are significantly influenced by the glycopolymer architecture, valency, size, and density of binding elements. In this context, these advanced and selected glyco-polymers/particles showing specific interactions with various lectins are highlighted.